Detection of thiabendazole fungicide/parasiticide by SERS: Quantitative analysis and adsorption mechanism - Oliveira, Marcelo J.S. [UNESP] (2020)
The application of surface-enhanced Raman scattering (SERS) as analytical tool remains a challenge due signal intensity fluctuations, which depends on experimental parameters such as size, shape, and aggregation of the metallic nanoparticles responsible for enhancing the Raman signal. Colloidal nanoparticles can overtake this difficulty by optimizing some experimental conditions for each analyte. Here, we applied SERS as analytical technique to detect thiabendazole (TBZ) at low concentrations using Ag colloid. TBZ stock solutions were added into Ag colloids and SERS spectra were recorded in triplicate. Within the TBZ concentration from 1.6 × 10−7 to 8.0 × 10−8 mol/L a linear regimen for SERS intensity was achieved, leading to a TBZ limit of detection of 13.8 ppb. Besides, the main enhanced bands of the TBZ SERS spectrum suggest the TBZ adsorption mechanism on Ag surface takes place by the thiazole moiety. Theoretical calculations support the experimental data and indicate the interaction is stablished by S atom. Complementary to analytical application and adsorption mechanism, the dependence of SERS intensity on TBZ concentration follows a sigmoidal adsorption isotherm, which has a direct relation with the extinction spectra of Ag colloid containing TBZ at different concentrations, revealing intermolecular TBZ interactions and formation of Ag nanoparticle aggregates with distinct morphologies.